2008
DOI: 10.1016/j.biopsycho.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Provisional hypotheses for the molecular genetics of cognitive development: Imaging genetic pathways in the anterior cingulate cortex

Abstract: Brain imaging genetic research involves a multitude of methods and spans many traditional levels of analysis. Given the vast permutations among several million common genetic variants with thousands of brain tissue voxels and a wide array of cognitive tasks that activate specific brain systems, we are prompted to develop specific hypotheses that synthesize converging evidence and state clear predictions about the anatomical sources, magnitude and direction (increases vs. decreases) of allele-and task-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…The QMT-induced structural changes are consistent with previous results observed after long-term motor and mental training (Draganski et al, 2004;H€ olzel et al, 2011;Scholz et al, 2009;Vestergaard-Poulsen et al, 2009). The cerebellar reorganization is most likely related to sensorimotor coordination and attention (Fossella et al, 2008;H€ olzel et al, 2011) required in the QMT. The FA increases in the corpus callosum may be related to a more efficient interhemispheric connection and increased alpha activity, as previously found following QMT (Ben-Soussan et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The QMT-induced structural changes are consistent with previous results observed after long-term motor and mental training (Draganski et al, 2004;H€ olzel et al, 2011;Scholz et al, 2009;Vestergaard-Poulsen et al, 2009). The cerebellar reorganization is most likely related to sensorimotor coordination and attention (Fossella et al, 2008;H€ olzel et al, 2011) required in the QMT. The FA increases in the corpus callosum may be related to a more efficient interhemispheric connection and increased alpha activity, as previously found following QMT (Ben-Soussan et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Moderating effects of genetic factors on treatment outcomes have received considerable attention in recent years. There is a growing body of literature showing that at least four genes (DRD4, DAT, COMT, and MAOA) are involved in attention networks in the brain (Fossella et al 2008). Rueda et al (2005) found that the long form of the dopamine transporter gene was associated with stronger effortful control in an attention training study.…”
Section: Implications For the Development Of Interventionsmentioning
confidence: 99%
“…These advances have profound implications for the development of novel intervention methods for children with children with FASD. For example, researchers have obtained evidence for genetic variation in executive attention (Fan et al, 2003; Fossella et al, 2008). In particular, there is evidence that alleles in a number of dopamine genes (e.g.…”
Section: Guidelinesmentioning
confidence: 99%